Teaching Medical Students in a New Rural Longitudinal Clerkship: Opportunities and Constraints - Marietjie de Villiers; Hoffie Conradie; Susan van Schalkwyk (Ubiquity Press, 2018)
Background: Medical schools in Africa are responding to the call to increase numbers of medical graduates by up-scaling decentralized clinical training. One approach to decentralized clinical training is the longitudinal integrated clerkship (LIC), where students benefit from continuity of setting and supervision. The ability of family physician supervisors to take responsibility for the clinical training of medical students over a longer period than the usual, in addition to managing their extensive role on the district health platform, is central to the success of such training. Objective: This study investigated the teaching experiences of family physicians as clinical supervisors in a newly introduced LIC model in a rural sub-district in the Western Cape, South Africa. Method: Nine semi-structured interviews were conducted with six family physicians as part of the Stellenbosch University Rural Medical Education Partnership Initiative (SURMEPI) five-year longitudinal study. Code lists were developed inductively using Atlas.ti v7, they were compared, integrated, and categories were identified. Emerging common themes were developed. Findings: Three overarching themes emerged from the data, each containing subthemes. The rural platform was seen to be an enabling learning space for the LIC students. The family physicians' experienced their new teaching role in the LIC as empowering, but also challenging. Lack of time for teaching and the unstructured nature of the work emerged as constraints. Despite being uncertain about the new LIC model, the family physicians felt that it was easier to manage than anticipated. Conclusion: The centrality of the rural context framed the teaching experiences of the family physicians in the new LIC, forming the pivot around which constraints and opportunities for teaching arose. The African family physician is well positioned to make an important contribution to the upscaling of decentralized medical training, but would need to be supported by academic institutions and health service managers in their teaching role.